Novel insights into the study of goblet cell hypersecretion in allergic rhinitis - Zhu, Xiaojia; Cheng, Fengli; Duan, Hongying; Fu, Sirui; Zhao, Changqing (Frontiers in Immunology, 2025)
Goblet cell hypersecretion is a hallmark of airway inflammation and is driven by complex neuroimmune regulation involving submucosal glands and goblet cells. Although studies have focused on mast cell degranulation as a critical driver of nasal secretion, the role of goblet cells in this process is relatively under-researched. In allergic airway inflammation, goblet cells exhibit metaplasia and hypersecretion. However, allergen exposure does not directly trigger goblet cell degranulation, raising questions regarding the underlying mechanisms of these reactions. The activation of enteric neurons promotes goblet cell degranulation by stimulating the calcitonin gene-related peptide (CGRP)–receptor active modification protein-1 (RAMP1) axis. Meanwhile, airway goblet cells express various neuropeptide receptors, and their activation by neuropeptides such as substance P and CGRP induces mucus secretion, exacerbating allergic rhinitis-associated hypersecretion. Thus, although previously less recognised, the neuron–goblet cell signalling axis plays a critical role in allergic rhinitis mucus secretion. This review highlights current research on the neuroimmune mechanisms underlying goblet cell metaplasia and degranulation, focusing on allergic rhinitis, so as to guide clinical treatment strategies.